2007
DOI: 10.1002/mds.21870
|View full text |Cite
|
Sign up to set email alerts
|

Impaired intracortical inhibition in the primary somatosensory cortex in focal hand dystonia

Abstract: Somesthetic temporal discrimination (STD) is impaired in focal hand dystonia (FHD). We explored the electrophysiological correlate of the STD deficit to assess whether this is due to dysfunction of temporal inhibition in the somatosensory inhibitory pathway or due to dysfunction in structures responsible for nonmodality-specific timing integration. Eleven FHD patients and 11 healthy volunteers were studied. STD threshold was investigated as the time interval required for perceiving a pair of stimuli as two sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 30 publications
4
72
2
3
Order By: Relevance
“…This implies that the somatosensory processing from the peripheral to primary somatosensory cortex in patients with WC is relatively preserved. However, loss of somatosensory inhibition at spinal and cortical levels in patients with WC was discovered under paired-pulse with an interstimulus interval of 5 to 40 ms [40], [41]. In present study, the interstimulus interval is 3 s. The N20m and P35m deflections might have been able to recover fully after each stimulus after such a time interval [42].…”
Section: Discussionmentioning
confidence: 42%
“…This implies that the somatosensory processing from the peripheral to primary somatosensory cortex in patients with WC is relatively preserved. However, loss of somatosensory inhibition at spinal and cortical levels in patients with WC was discovered under paired-pulse with an interstimulus interval of 5 to 40 ms [40], [41]. In present study, the interstimulus interval is 3 s. The N20m and P35m deflections might have been able to recover fully after each stimulus after such a time interval [42].…”
Section: Discussionmentioning
confidence: 42%
“…In healthy subjects, active movements reduce the amplitude of somatosensory evoked potentials (pre-movement gating) but in patients with hand dystonia, pre-movement gating is absent, suggesting an abnormality in the interaction between motor and sensory cortical areas 22. Furthermore, studies investigating the inhibitory functions of the sensory system with the technique of somatosensory evoked potentials reported altered inhibitory functions within the somatosensory system and, in particular, a loss of short latency inhibitory mechanisms in primary sensory cortex, leading to impaired afferent–input gating in dystonia 23 24. Afferent–input gating plays a role in the spatio-temporal separation of two incoming stimuli and allows information to be processed separately 25.…”
Section: Discussionmentioning
confidence: 99%
“…26,[29][30][31] Sensory Discrimination Paradigms in Primary Adult Onset Dystonia Several studies have revealed an abnormal tactile TDT in generalized and focal dystonias, including blepharospasm, cervical and focal hand dystonia. [24][25][26][27][28][29][30][31][32][33] TDT alterations were observed not only in the affected body regions but also in parts remote from dystonic symptoms. These findings hint at a disorder in processing cutaneous inputs and may relate to deficits of kinesthesia, graphesthesia and stereognosis found in dystonia.…”
Section: Sensory Discrimination Paradigmsmentioning
confidence: 95%
“…[19][20][21][22][23] Recent behavioral studies have shown that these sensory functions are compromised in patients with several forms of primary dystonia. Changes have been found in: (1) temporal discrimination and integration of sensory signals [24][25][26][27][28][29][30][31][32][33] ; (2) spatial discrimination of tactile stimuli 28,[34][35][36][37][38] ; (3) vibration-induced illusion of movements [39][40][41][42] ; and (4) movement representation and learning. [43][44][45][46] In this review, we focus on the possible role of abnormal sensory processing in the pathophysiology of primary dystonia, highlighting potential implications for innovative therapeutic strategies to aid functional recovery.…”
Section: Introductionmentioning
confidence: 99%